CREATIVE ADS STRATEGY OF BLANJA.COM TO WIN E-COMMERCE MARKET THROUGH YOUTUBE - Velda Ardia; Fanisah Nur Fadilah (Universitas Muhammadiyah Jakarta, 2019)
Today’s business competition among e-commerce companies heating up, Blanja.com compete with other aggres- sive e-commerce in advertising. The right advertising creative strategy is required. In that regard, the mentioned- creative advertising strategy uses one of social media asset namely Youtube. The purpose of this study is to ana- lyze the creative advertising strategy of one of the e-commerce in Indonesia, Blanja.com on Youtube as well as to identify the reasons of using Youtube behind its creative advertising strategies. Relevant theories of this study consist of advertising theory, creative advertising strategies, new media, youtube and e-commerce. This research method uses descriptive qualitative with data collection through interviews. In the research there was one key informant namely the Blanja.Com Brand Manager, as well as three other informants for data triangulation. They are all advertising practitioners from Bujukrayu agency, Harsi Lima Agency, dan dari Morzel Digital. The results showed that the Blanja.Com advertisement version of